Synthesis, purification and microstructural characterization of nickel doped carbon nanotubes for spintronic applications. Issue 5 (April 2016) - Prakash, Deo; Amente, Chernet; Dharamvir, Keya; Singh, Bedvir; Singh, Rishipal; Shaaban, E.R.; Al-Douri, Y.; Khenata, R.; Darroudi, Majid; Verma, K.D.
Abstract: The formation of nickel doped carbon nanotubes (Ni/CNTs), using the arc discharge method in open air deionized water is reported. The formation of Ni/CNTs was confirmed by Raman spectroscopy. Transmission Electron Microscopy (TEM) was used to examine the morphology of the system at different synthesis stages. Energy dispersion X-ray spectroscopy (EDX) was employed for elemental determination. According to the study, CNTs are self-assembled with the tangled carbonaceous system, with entanglement being overwhelming where metallic concentration is lower in the absence of acidic treatment.